Esther Greenwood's Psychological Conflicts Reflected In Sylvia Plath's The Bell Jar(1963): A Psychoanalytic Criticism - Fadlila, Zenithda Arief, Dr. M. Thoyibi, M.S, Titis Setyabudi, SS (2013)
Psychoanalysis is a branch of psychology. Psychoanalysis is a psychology of the unconscious; its interests were in the areas of motivation, emotion conflict, neurotic symptoms, dreams, and character traits. Psychoanalysis focuses its study on human being. The objectives of the study are to identify the indicator of Esther's psychological conflict, to identify what causes the psychological conflict in the self of Esther, and to explain the way Esther tries to solve the problem of her psychological conflict. In analyzing the novel, the writer uses Sigmund Freud's Psychoanalysis Criticism, and qualitative research. The object of the study is The Bell Jar by Silvia Plath. Types of data and data source are divided into two categories, primary data and secondary data. The primary data source is taken from the novel The Bell Jar by Sylvia Plath. The secondary data are taken from official website, related theories, etc. The outcome of the study shows that Sylvia Plath illustrates a psychological phenomenon when an individual experiences an inner conflict because the differences desire in her. She attempts to cover her conflict uses aggression. Aggression is the way to solve the problem by ending the life. She is inclined to use a physical aggression; a forceful action especially when intended to dominate.